Prevalence of mental disorders and psychological trauma among conflict- affected population in Somalia: a cross-sectional study - Salad, Abdulwahab M; Malik, SK Md Mamunur Rahman; Ndithia, James Mwangi; Noor, Zeynab; Madeo, Marina; Ibrahim, Mohamed (Frontiers in Public Health, 2023)
Background: Despite the longstanding psychosocial impact of the interactable conflict in Somalia for the last 30 years, there is lack of epidemiological studies of mental health conditions, especially at the population level. Objectives: The aim of this study is to fill the epidemiological gap and provide population based data on mental health conditions in the South-Central region of Somalia. The specific objectives were: 1) To determine the epidemiological patterns of mental disorders in three sites; Baidoa, Dolow and Kismayo; 2) Understand the socio-demographic characteristics associated with mental health conditions in the study sites; 3) To assess the correlates between psychological trauma and the mental wellbeing of the population Methods: This was a cross-sectional study of 713 respondents recruited from the three sites namely Dolow, Baidoa and Kismayo. Data on sociodemographic characteristics and mental disorders were collected using the MINI and sociodemographic questionnaire. Basic descriptive statistics were used to summarize sociodemographic characteristics. Univariable and multivariable logistic regressions were used to examine factors associated with common mental disorders. Statistical significance was considered at a p-value <0.05. Results: Participants' mean age was 32.6 (±10.7) years. More than half (58.5%) of the respondents were male. The overall prevalence of common mental disorders was 557(78.1%) with panic disorder (39.3%), generalized anxiety disorders (34.9%), major depressive episode current (32.1) and PTSD (29.9%). According to the multivariable logistic regression analysis, being male AOR=1.74 (95%CI=1.25, 2.42), having a family size of more than 10 members AOR =1.37 (95% CI=1.00, 1.89), being unemployed AOR=1.90 (95%CI=1.18, 3.06), experienced starvation AOR =3.46 (95%CI=2.23, 5.37), khat use AOR=5.87 (955 CI,, were identified as predicting factors for the common mental disorders among the study participants. Conclusion: There is a high prevalence of mental disorders with anxiety disorders being the commonest. Findings reflect earlier studies that showed higher rates in conflict and post-conflict settings. It also aligns with past studies in Somalia. As such, there is an urgent need to integrate mental health and psychosocial support within the primary healthcare and other service sectors such as education considering the vast majority of the population are young.